Управління екологічними проектами (за матеріалами ТОВ Нова пошта) - Йосифчук, Ярослав Миколайович; Yosyfchuk, Yaroslav Mykolayovych (Ірпінь, 2023)
У роботі обґрунтовано теоретико-методологічні засади та розроблено практичні рекомендації щодо управління екологічними проектами на базі ТОВ «Нова Пошта». Розглянуто теоретико-методичні основи управління екологічними проектами, аналіз системи правління екологічними проектами ТОВ «Нова Пошта» та розроблено пропозиції щодо вдосконалення системи управління екологічними проектами ТОВ «Нова Пошта». Сформульовані відповідні висновки та пропозиції. Одержані результати можуть бути використані у подальшій діяльності ТОВ «Нова Пошта».

The paper substantiates the theoretical and methodological foundations and develops practical recommendations for managing environmental projects on the basis of Nova Poshta LLC. The theoretical and methodological foundations of environmental project management, analysis of the system of management of environmental projects of "Nova Poshta" LLC are considered, and proposals for improving the system of management of environmental projects of "Nova Poshta" LLC are developed. Relevant conclusions and suggestions are formulated. The results obtained can be used in the further activities of Nova Poshta LLC.
Environmental project management (according to the materials of Nova Poshta LLC)
Keywords: управління проектами; екологічні проекти; життєвий цикл; екологічний менеджмент; SWOT-аналіз; projects management; environmental ( ecological) projects; life cycle; ecological management; SWOT- analysis